ENT300 Fundamental of Entrepreneurship. Business Plan : Bitsy Clean Enterprise / Erna Zurainah Kamalin... [et al.] - Kamalin, Erna Zurainah; Marzuki, Aisyah Hanania; Wan Hassan, Sh. Nur Hidayah; Baba, Jumriyanie; Hassan, Norkhaleeda (2014)
After doing extensive research on the business opportunity in Matang, Kuching, our group has decided to specify our business to giving service which is cleaning service for house and office. Our group has come up with the business plan of partnership whereby our company’s name will be known as Bitsy Clean Enterprise. Our main office will be located at 811, Lot 6961, Section 65, Mile 4 1/2, Jalan Matang, Kuching, 93050, Kuching, Sarawak. Bitsy Clean Enterprise is a form of partnership business which consist of 5 shareholders. Each shareholders will need to contribute a certain amount of capital that has been agreed. The selection of partners are based on their personal skills, qualification, and their field of expert. Each shareholders are also allowed to involve in the management and daily operation of the business. In other to make to business to become successful, we have set our objectives for the organization to maximize our profit, minimize the cost of production and achieve highly standards so that our company will be able to compete with other leading competitors. We also would set our company to be the leading company for giving the best cleaning service and be the number one customer’s choice for cleaning service. In addition, to establish and launched this business, we need total project implementation coast amounted from loan RM39,433 from the SME Bank and contribution of RM10,000 from the shareholders.